2016
DOI: 10.1007/s00415-016-8201-5
|View full text |Cite
|
Sign up to set email alerts
|

Pathological laughing and crying in amyotrophic lateral sclerosis is related to frontal cortex function

Abstract: The syndrome of pathological laughing and crying (PLC) is characterized by episodes of involuntary outbursts of emotional expression. Although this phenomenon has been referred to for over a century, a clear-cut clinical definition is still lacking, and underlying pathophysiological mechanisms are not well understood. In particular, it remains ill-defined which kind of stimuli-contextually appropriate or inappropriate-elicit episodes of PLC, and if the phenomenon is a result of a lack of inhibition from the fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…However, it is considered to be a disconnection syndrome, which results in the loss of brainstem inhibition in a putative control center on crying and laughter [58]. It is also associated with greater cognitive deficits mediated by the frontal lobe [59]. Usually it is more frequent among patients with greater physical incapacity and in more advanced stages of the illness [2].…”
Section: Psychiatric Disordersmentioning
confidence: 99%
“…However, it is considered to be a disconnection syndrome, which results in the loss of brainstem inhibition in a putative control center on crying and laughter [58]. It is also associated with greater cognitive deficits mediated by the frontal lobe [59]. Usually it is more frequent among patients with greater physical incapacity and in more advanced stages of the illness [2].…”
Section: Psychiatric Disordersmentioning
confidence: 99%
“…Survival analysis was performed on a total of 94 cases. 25 The study of Floeter and coworkers showed that patients with ALS and PBA presented disruption of descending fiber tracts from the frontotemporal cortex toward the pons. Demographic and clinical parameters of the cohort considered for the analysis, along with group comparisons according to CNS-LS total score (</≥13), are reported in Table 1 tern of the disease.…”
Section: Re Sultsmentioning
confidence: 99%
“…Another hypothesis is that PBA may be related to frontal cortex dysfunction. 25 The study of Floeter and coworkers showed that patients with ALS and PBA presented disruption of descending fiber tracts from the frontotemporal cortex toward the pons. 21 Frontal circuits are also involved in executive and social cognition deficits, both common in ALS and both related to a poorer prognosis.…”
Section: Re Sultsmentioning
confidence: 99%
“…This condition may arise from the disconnection of brainstem structures from cortical inhibition and can occur in several neurological diseases, such as strokes, traumatic brain injuries, Alzheimer’s disease, multiple sclerosis, amyotrophic lateral sclerosis (ALS), and primary lateral sclerosis (PLS) (Finegan et al, 2019 , 2021 ; Parvizi et al, 2006 , 2009 ; Work et al, 2011 ). At the population level, up to 50% of patients with motor neuron diseases, and in particular those with bulbar upper motor neuron (UMN) involvement, are affected by this condition, and one-third of ALS patients present PBA at diagnosis (Tortelli et al, 2016 ; Hübers et al, 2016 which represents a negative prognostic symptom (Barć et al, 2020 ; Tortelli et al, 2018 ). However, although PBA is a frequent and long-reported symptom, it has remained unclear if this phenomenon is a result of a lack of inhibition from the frontal cortex ("top-down-theory") or due to altered processing of sensory inputs at the brainstem level ("bottom-up-theory") (Bede & Finegan, 2018 ).…”
Section: Introductionmentioning
confidence: 99%